2005
DOI: 10.2739/kurumemedj.52.29
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Alterations of Submandibular Glands Caused by Cisplatin in the Rat

Abstract: Cisplatin is a platinum-containing antineoplastic agent, widely used in the treatment of various malignant neoplasms including head and neck cancer. In this study we examined ultrastructural changes of rat submandibular glands (SMGs) after cisplatin treatment. Male Wistar rats aged 8 weeks were used in the experiments. Cisplatin was injected intraperitoneally into the rats (5 mg/kg/day) for three consecutive days. After 1, 3, 5, and 7 days, the SMGs were removed and observed under an electron microscope. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
8
14
0
Order By: Relevance
“…On the seventh day after infusion, the shape of the acinar cells remained irregular, but the number of secretory granules increased. 2 Hey et al reported that prospective non-randomized study the influence of concomitant radio-chemotherapy with cisplatin tends to cause a higher probability of complication compared to radiotherapy alone. 15 Yamamoto et al reported that, according to their in vitro experimental study, one can assume that cisplatin has enough potential to considerably damage the salivary gland tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the seventh day after infusion, the shape of the acinar cells remained irregular, but the number of secretory granules increased. 2 Hey et al reported that prospective non-randomized study the influence of concomitant radio-chemotherapy with cisplatin tends to cause a higher probability of complication compared to radiotherapy alone. 15 Yamamoto et al reported that, according to their in vitro experimental study, one can assume that cisplatin has enough potential to considerably damage the salivary gland tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutics may lead to directly or indirectly changes in oral mucosa and minor salivary glands. 1,2 The mucositis status secondary to the stomatotoxic effects of chemotherapeutic agents increases the morbidity and cost of treatment in cancer patients. Swallowing dysfunctions and altered saliva production are common sequelae of radiation with or without chemotherapy in the management of head and neck cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucositis, fungal infections, salivary secretion dysfunctions, and neuropathies are signs of early oral side effects (2) . Also; it leads to morphologic damage in salivary gland tissue (3) . Saliva is a fluid of the oral cavity produced by salivary glands with many functions.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-quantitative analysis of expression of TFF1, TFF2 and TFF3 mRNA was analyzed semi-quantitatively based on the absorbance of TFF1, TFF2 and TFF3 compared to that of β -actin. TTT ATT C T TFF2 297 NM_053844 TCT TGG TAG TGG TCC TTG TCT TG 55 GAA GAT CAG GTT GGA AAA GCA G TFF3 193 NM_013042 ATG GAG ACC AGA GCC TTC T 58 GGA TGC TGG AGT CAA AAC AG β -actin 452 NM_031144 TCA GGT CAT CAC TAT CGG CAA T 57 AAA GAA AGG GTG TAA AAC GCA Kitashima 2005). We observed that the acinar cells of the SMG stained positive for PAS and faintly positive for AB, while the cells of the duct system reacted weakly with PAS, which verifi ed that SMG acinar cells are seromucous.…”
Section: Rt-pcr Analysismentioning
confidence: 99%